2006
DOI: 10.1590/s0101-20612006000200003
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação de melão minimamente processado armazenado em diferentes temperaturas e embalagens

Abstract: O Brasil é o terceiro maior produtor de melão da América Latina. O País passou de importador a grande produtor e, posteriormente, a exportador para os mercados europeus e norte-americano, sendo que cerca de 20% da produção nacional é destinada à exportação. A Região Nordeste responde por 97,70% da produção nacional [1] SUMMARY EVALUATION OF MINIMALLY PROCESSED MELON STORED AT DIFFERENT TEMPERATURES AND PACKAGES.The minimally processed products offer several benefits for consumers, such as the reduction of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 4 publications
1
3
0
2
Order By: Relevance
“…This result was similar to the one found by Pizarro (2003) who tested consumer preference for PET or PVC packaging of honeydew melon, and found that 71% favored the PET packaging. Dantas et al (2005), when researching the willingness to buy minimally processed products noted that the possibility of a better visualization of the product inside the packaging did not affect significantly the consumer's willingness to buy.…”
Section: Methodssupporting
confidence: 89%
“…This result was similar to the one found by Pizarro (2003) who tested consumer preference for PET or PVC packaging of honeydew melon, and found that 71% favored the PET packaging. Dantas et al (2005), when researching the willingness to buy minimally processed products noted that the possibility of a better visualization of the product inside the packaging did not affect significantly the consumer's willingness to buy.…”
Section: Methodssupporting
confidence: 89%
“…A greater variation was observed in the treatment T1, being that it differed significantly from the other treatments for the evaluated attributes, demonstrating that the xanthan gum (T2) and chitosan (T3) succeeded in delaying the changes that degrade and diminish the quality of minimally processed broccoli. Pizarro et al (2006) working with different plastic packages found values of odor lower to the other treatments in comparison with the control sample. These results are not in agreement with the present study, because higher values were found on the last day of storage for the remaining treatments (T2 and T3) in relation to the control sample.…”
Section: Sensory Analysismentioning
confidence: 66%
“…Sensory analysis performed by Pizarro et al () found lower values for aroma (odor) compared to the control sample when working with different plastic packages. These results are not in agreement with the present study, because larger values were found on the last day of storage for the other treatments (T2 and T3) in relation to the control sample of the present study.…”
Section: Resultsmentioning
confidence: 99%
“…From the fifth day of storage, differences in pH values between some treatments were observed. According to Pizarro, Benedetti, and Haj‐Isa (), this may be related to important biochemical deteriorations (lactic fermentation) and may be signs of microbial contamination.…”
Section: Resultsmentioning
confidence: 99%